Towards a phygital heritage approach for museum collection - Lo Turco, Massimiliano; Giovannini, Elisabetta Caterina (Journal of archaeological science, reports, 2020)
•Digital applications for museum collections.•Data interoperability between Museum and Collections.•Prefiguring the visitor flows and mapping the visitors' behaviour. The paper presents different experiences developed at the Department of Architecture and Design of Politecnico di Torino in collaboration with Fondazione Museo delle Antichità Egizie in Turin, Italy. These research offered interesting suggestions for working on the crucial relationship between content (collection) and container (museum) through shared and interoperable digital workflows. In the B.A.C.K. TO T.H.E. F.U.T.U.RE. project the research emphatise the role of artworks, that are characterized by intangible and historical values. Artworks are also connected with eterogeneous documentary heritage that enlighted the need of creating new narratives avoiding the descriptive and analytical ones. The project offers a workflow that using different vocabularies (database and open data) is able to structure data and use visual media (3d web publishing) to create different degree of accessibility to cultural heritage content. The recently launched SMART MUSEUM research, works on automated procedures to show, through graphics, the complex phenomena triggered by the attractive weight of the collections. In this case, the artwork assumes artistic, social and media values that contribute to create novel attributes able to identify an attractive weight of the artwork. These value affects the attractiveness of an artwork within the exhibition project and can be an interesting subject for a correct foreshadowing of visitor flows. The involved elements are the exhibition area (the graphic field), the collection (the attractive elements) and the users. The conceived procedure, once automated, becomes a prototype to support the curators to control and improve the efficiency of the exhibition layout.